(Ga55In45)2S300 Nanocrystallites as Novel Materials for Nonlinear Optical Detection of Gamma Radiation. (6th April 2018) - Kityk, I.V.; Ozga, K.; Halyan, V.; Ivashchenko, I.A.; Piasecki, M.
ABSTRACT: (Ga55 In45 )2 S300 and (Ga54.59 In44.66 Er0.75 )2 S300 single crystals were successfully grown with the aim of exploring their potential for laser induced third harmonic generation (THG) and piezo-optical applications. Their Raman and luminescence spectra in the 150-300 K temperature range were studied. Influence of different gamma ray doses on the nonlinear optical properties were also explored. The optical properties of these crystals exhibit strong variation with temperature. It is concluded that (Ga54.59 In44.66 Er0.75 )2 S300 may be applied as promising materials for dosimetry applications in γ - radiation and optical temperature sensors.